SEGREGATED ELECTRICALLY CONDUCTIVE NANOCOMPOSITES BASED ON THERMOPLASTIC ELASTOMERS AND GRAPHITE - Kakhramanov, Najaf T.; Allahverdiyeva, Khayala V.; Gahramanli, Yunis N.; Mustafayeva, Fatima A.; Sadikhov, Nazim M.; Martynova, Galina S.; Valimatova, Naida I.; Gurbanova, Rena V. (ChemChemTech, 2024)
The paper presents the results of a study of the electrical conductive characteristics and a complex of physical-mechanical properties of graphite-based nanocomposites, a wide range of polyolefins - low-density polyethylene, high-density polyethylene, isotactic polypropylene, random copolymer of polypropylene, block copolymer of propylene with ethylene, ethylene/hexene copolymer and ethylene/butene-1 copolymer. For the considered nanocomposites based on polyolefins, the optimal concentrations of graphite were determined, at which the maximum values of electrical conductivity are achieved, within the range of 10–2–10–3 (Ωm)–1. A detailed description of the mechanism of tunneling and electronic electrical conductivity in the nanocomposites under consideration is given. Thermoplastic elastomers (TPE) based on polyolefins and ethylene-propylene-diene rubber have been developed. In a wide concentration range, the regularities of changes in the electrical conductivity of nanocomposites based on thermoplastic elastomers and nanodispersed graphite have been determined. When studying the physical-mechanical properties of TPE nanocomposites, the tensile strength, yield strength, elongation at break, bending strength, Vicat softening temperature, melt flow rate, and Young's modulus were determined. The regularity of the change in the dependence "stress-strain" for TPE depending on the content of ethylene-propylene-diene rubber has been established. Using the methods of derivatography, X-ray phase and SEM analyses, and electron microscopy, studies were carried out to assess the structural features of nanocomposites of thermoplastic elastomers depending on the ratio of the mixture components used. For visual interpretation, a schematic representation of the processes occurring in the interfacial region of thermoplastic elastomers is given. The method of X-ray phase analysis shows the regularity of the change in the degree of crystallinity of thermoplastic elastomers depending on the content of rubber and graphite. The principal possibility of obtaining flexible electrically conductive materials with predetermined properties by controlling the ratio of components in the composition of thermoplastic elastomers is shown. For citation: Kakhramanov N.T., Allahverdiyeva Kh.V., Gahramanli Yu.N., Mustafayeva F.A., Sadikhov N.M., Martynova G.S., Valimatova N.I., Gurbanova R.V. Segregated electrically conductive nanocomposites based on thermoplastic elastomers and graphite. ChemChemTech [Izv. Vyssh. Uchebn. Zaved. Khim. Khim. Tekhnol.]. 2024. V. 67. N 11. P. 122-137. DOI: 10.6060/ivkkt.20246711.7045.